Browder's convergence theorem for multivalued mappings without endpoint condition - Dhompongsa S. (2014)
We prove Browder's convergence theorem for multivalued nonexpansive mappings in a complete R-tree without endpoint condition. This gives an affirmative answer to Jung's question for nonlinear spaces. © 2012 Elsevier B.V.